Evaluating the Impact of Physiologically Relevant Oxygen Tensions on Drug Metabolism in 3D Hepatocyte Cultures in Paper Scaffolds. Issue 2 (17th February 2023) - Sitte, Zachary R.; DiProspero, Thomas J.; Lockett, Matthew R.
Abstract: Oxygen is an essential regulator of cellular function and phenotype. Despite its importance, the incorporation of physiologically relevant oxygen tensions is often overlooked in experimental setups. Ambient oxygen tensions (pO2 ∼152 mmHg) are significantly higher than those in the alveolar‐capillary barrier of the lung, which is the most oxygen‐rich interface in the body (pO2 ∼104 mmHg). The discrepancy between standard culture practices and physiologically relevant oxygen tensions is more pronounced when considering the hepatocyte‐lined sinusoids of the liver, whose pO2 values range from 65 mm Hg in the periportal region to 30 mm Hg in the perivenous region. Our previous work highlights the need to transition from standard culture conditions to more physiologically relevant microenvironments when predicting hepatocyte responses to drug candidates or potential toxins. This protocol details an experimental pipeline for quantifying differences in transcript levels, protein levels, and activity of the cytochrome P450 1A (CYP1A) enzyme family in hepatocytes maintained in a three‐dimensional environment at ambient and physiologically relevant oxygen tensions. We quantify changes in transcript with qRT‐PCR, protein expression with western blots, and activity with the ethoxyresorufin‐O‐deethylase (EROD) assay. This approach can be adapted to any drug‐metabolizing enzyme. © 2023 Wiley Periodicals LLC. Basic Protocol 1 : Preparing tissue‐like environments to evaluate HepG2 cells in paper‐based cell culture platform at physiological oxygen levels Basic Protocol 2 : Evaluating CYP1A activity of hepatocytes grown in the paper scaffolds using the EROD assay Basic Protocol 3 : Evaluating CYP1A transcript levels of hepatocytes grown in the paper scaffolds using RT‐qPCR Basic Protocol 4 : Evaluating CYP1A protein levels of hepatocytes grown in the paper scaffolds using western blotting